#### Answer

The equation has no real solutions. Hence, it has no points.

#### Work Step by Step

Write
${x^2} + 3{y^2} - 6x + 12y + 23 = 0$
${x^2} - 6x + 3{y^2} + 12y + 23 = 0$
${\left( {x - 3} \right)^2} - 9 + 3{\left( {y + 2} \right)^2} - 12 + 23 = 0$
${\left( {x - 3} \right)^2} + 3{\left( {y + 2} \right)^2} + 2 = 0$
${\left( {x - 3} \right)^2} + 3{\left( {y + 2} \right)^2} = - 2$
The left-hand side is nonnegative because it is the sum of two squares. But the right-hand side is negative, so there is no real solutions. Hence, it has no points.